Netnografi Digital Slang: Dinamika dan Faktor Viralitas Tren Bahasa Gen Z di Platform X - Silvi; Hasanah, Ninah; Loekman, Arief (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of social media has transformed the ways in which young generations form and use language in digital spaces. Platform X represents one example of this dynamic, as it demonstrates diserve, creative, and context-sensitive language practices. This study aims to describe the forms of slang language variations used by Gen Z on platform X and to explain the factors that encourage the emergence of these slang variations as trends from digital sosiolinguistic perspective. The research employes as a descriptive qualitative method with a netnographic approach. The data sources consist of post and interactions by Gen Z users on platform X that contain slang expression. Data collections techniques include social media observation and documentation. The findings reveal that slang language variations used by Gen Z on platform X involve the creation of new terms. The variations are influenced by several factors, including social identity, linguistic creativity, and the distinctive characteristics of digital communication. The findings indicate that slang language on platform X functions not only as a communication tool but also as a means expressing identity and reinforcing social membership among Gen Z.